Radiation Hardness of Mos Structures Exposed to High-Energy Ions - Ladislav Harmatha; L. Stuchlikova; P. Pisecny (Communications - Scientific letters of the University of Zilina, 2006)
MOS structures exposed to 305 MeV Kr and 710 MeV Bi ions irradiation with fluences of 109 cm2 and 1010 cm2 were investigated by capacitance measuring methods (C–V, C–t), completed by quasistatic low-frequency C–V and DLTS measurements.The irradiated MOS structures were functional in spite of a high density of radiation defects. The electric activity of the defects brought a sharp decrease in the generation parameters tr and g. The parameters of six deep levels were detected in the MOS structures exposed to 710 MeV Bi ions irradiation. Five of these levels with energies 0.52 eV, 0.14 eV, 0.17 eV, 0.25 eV, 0.27 eV were radiation defects.